Перспективи інтродукції видів та культиварів лілійнику (Hemerocallis L.) в умовах степового Придніпров’я - Chipilyak, T.F. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
In article to grounding the perspectives of introductions of the genus Hemerocallis L. representatives in conditions of Steppe Pridnieprovie. The data of observations of rhythms of flowering, the analysis of decorative values of introduced species and adaptation ability of the genus Hemerocallis L. representatives are given.